2003
DOI: 10.14783/maruoneri.681821
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Job Stress and Work-Family Conflict

Abstract: Today women an important part of the total workforce are women. The ones who are able to balance their work life and their family life can be very successful in their businesses. The aim of this study is to analyze the relationship between job satisfaction and job stress of female employees and to investigate the effects of marital status, presence, age and number of children on their job stress levels. In addition, the relationship between the demographic variables, age and educational levels of female employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Stress and conflict between work and family are equally positive. GÜRBÜZ & TOĞRAN (2020) investigated the relationship between job stress and work-family conflict. In this study, the researcher found that in today's era, women play an important role in the organization.…”
Section: Turnover Intentionsmentioning
confidence: 99%
“…Stress and conflict between work and family are equally positive. GÜRBÜZ & TOĞRAN (2020) investigated the relationship between job stress and work-family conflict. In this study, the researcher found that in today's era, women play an important role in the organization.…”
Section: Turnover Intentionsmentioning
confidence: 99%